1998
DOI: 10.1090/qam/1637056
|View full text |Cite
|
Sign up to set email alerts
|

Eigenoscillations of mechanical systems with boundary conditions containing the frequency

Abstract: Abstract.The problem of eigenoscillations of beam-mass systems is investigated and four examples are developed. For such systems the corresponding Sturm-Liouville problems contain the eigenvalue parameter in the boundary conditions. It is shown that the eigenfunctions for the systems considered form a basis of the appropriate Hilbert space. Rayleigh-Ritz formulas are also developed. Some lower bound estimations for eigenfrequencies are also found. Introduction.As is well known, the set of eigenfunctions of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The compactness of  is well-known fact (see, [34]). The proof of the compactness of 1  can be found by using the same arguments, as in [10,11] and [13].…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…The compactness of  is well-known fact (see, [34]). The proof of the compactness of 1  can be found by using the same arguments, as in [10,11] and [13].…”
Section: mentioning
confidence: 99%
“…Oscillation and comparison results have been obtained in [7]. The completeness of the eigenfunctions and eigenfunction expansions in various function spaces for the Sturm-Liouville problems with spectral parameter in the boundary conditions have been considered in [10][11][12][13][14][15][16]. Problems with various singularities have been analyzed in [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: mentioning
confidence: 99%
“…Theoretical results and applications of one-dimensional spectral problems with eigenvalue in the boundary conditions are presented in [2]. We begin with (18).…”
Section: Appendix a Spectral Problemsmentioning
confidence: 99%
“…Basis properties and eigenfunction expansions for Sturm-Liouville problems involving eigenparameter in the boundary conditions have been considered in [1,5,9,10,14,[27][28][29]. Aliyev and Kerimov [1] studied basisness of root functions of Sturm-Liouville problems with a boundary condition depending quadratically on the spectral parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Aliyev and Kerimov [1] studied basisness of root functions of Sturm-Liouville problems with a boundary condition depending quadratically on the spectral parameter. In [5], it is shown that the problem of eigenoscillations of various mechanical systems is formulated as the Sturm-Liouville problem with the eigenvalue parameter appearing in the boundary conditions. It is proven that the eigenfunctions form a Riesz basis of suitable Hilbert space.…”
Section: Introductionmentioning
confidence: 99%